1978
DOI: 10.1007/bf01287493
|View full text |Cite
|
Sign up to set email alerts
|

The role of awareness space in urban residential preferences: A case study of Venezuelan youth

Abstract: Empirical studies of inter-urban and interregional migration have most often assumed that objective place or personal characteristics affect the migration decision directly. Such studies tend to disregard the roles of awareness of opportunities at potential destinations, and of the preferences for these destinations which are a function of this awareness. In this study, the presence of six different types of direct and indirect contact with three potential destinations (large cities in Venezuela) is shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Despite such early work, little further research has advanced this theme in Third World countries (Potter, 1985a). Exceptions are provided by studies of Papua New Guinea (Weinand & Ward, 1979), Venezuela (Jones, 1978;Jones & Zannaras, 1978), Barbados (Potter, 1984), and Trinidad (Potter, 1983b). But the present authors are not aware of any research set in the developing world which has sought to examine how national space preferences and perception surfaces develop among young people.…”
mentioning
confidence: 84%
“…Despite such early work, little further research has advanced this theme in Third World countries (Potter, 1985a). Exceptions are provided by studies of Papua New Guinea (Weinand & Ward, 1979), Venezuela (Jones, 1978;Jones & Zannaras, 1978), Barbados (Potter, 1984), and Trinidad (Potter, 1983b). But the present authors are not aware of any research set in the developing world which has sought to examine how national space preferences and perception surfaces develop among young people.…”
mentioning
confidence: 84%
“…Past research has shown that individual awareness spaces are significantly affected by socioeconomic characteristics (White 1980). Aggregate awareness spaces have been shown to be highly correlated with migration streams to large urban areas (Jones and Zannaras 1978, White 1977, February 1981.…”
Section: A Return Migration Modelmentioning
confidence: 99%
“…Action spaces have been used to describe an individual's total interaction with his/her environment and they contain all locations about which an individual is aware of or has some knowledge [108,109]. Action space has also been referred to as "awareness space" in the literature [110,111]. Jakle et al [112] have divided the concept of action space into two meaningful components: movement and communication.…”
Section: Concept Of Activity Spacesmentioning
confidence: 99%